2022
DOI: 10.3201/eid2803.212210
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Breakthrough Infections after introduction of 4 COVID-19 Vaccines, South Korea, 2021

Abstract: We conducted a nationwide retrospective cohort study to estimate severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) breakthrough infection among recipients of 4 different vaccines in South Korea. Age-adjusted breakthrough infection rate per month was highest for Janssen (42.6/100,000 population), followed by AstraZeneca (21.7/100,000 population), Pfizer-BioNTech (8.5/100,000 population), and Moderna (1.8/100,000 population).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…The age at which individuals are more likely to develop a breakthrough infection is controversial, many studies reported higher rates of breakthrough among elderly hospitalized patients [ 8 , 17 , 18 ]. However, in accordance with our results, others concluded that young people are more liable to breakthrough infections [ 12 , 19 ]. It was suggested that the controversy between studies could be related to the type of vaccine used.…”
Section: Discussionsupporting
confidence: 93%
“…The age at which individuals are more likely to develop a breakthrough infection is controversial, many studies reported higher rates of breakthrough among elderly hospitalized patients [ 8 , 17 , 18 ]. However, in accordance with our results, others concluded that young people are more liable to breakthrough infections [ 12 , 19 ]. It was suggested that the controversy between studies could be related to the type of vaccine used.…”
Section: Discussionsupporting
confidence: 93%
“…Understanding the effectiveness of vaccines and the factors influencing breakthrough infections is key for informed decision-making and implementation of plans to control the epidemic and protect public health, especially during the upcoming waves of infection and for similar future events. Consistent with previous studies, our findings revealed variations in the effectiveness of different COVID-19 vaccine types against COVID-19 breakthrough infections, with the Pfizer (mRNA-based) vaccine outperforming the ASZ (DNA-based) vaccine [18] . Because different vaccine development platforms are based on triggering the immune response to produce neutralizing antibodies in different ways, the immune response is assumed to be different for each vaccine [19] .…”
Section: Discussionsupporting
confidence: 91%
“…Third, the prospects for economic and social losses due to the COVID-19 mutant virus and breakthrough infection are dim [ 33 , 34 ]. In addition to the present study, policy support for further research is needed to identify COVID-19 patients with a high risk of belonging to the clinical severity group at the earliest to prepare measures for the prevention and treatment of COVID-19 and manage medical resources efficiently.…”
Section: Discussionmentioning
confidence: 99%